Planar Microwave Sensors for Accurate Measurement of Material Characterization: A Review - Norhanani Abd Rahman; Zahriladha Zakaria; Rosemizi Abd Rahim; Yosza Dasril; Amyrul Azuan Mohd Bahar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Microwave sensor is used in various industrial applications and requires highly accurate measurements for material properties. Conventionally, cavity waveguide perturbation, free-space transmission, open-ended coaxial probe, and planar transmission line technique have been used for characterizing materials. However, these planar transmission lines are often large and expensive to build, further restricting their use in many important applications. Thus, this technique is cost effective, easy to manufacture and due to its compact size, it has the potential to produce sensitivity and a high Q-factor for various materials. This paper reviews the common characteristics of planar transmission line and discusses numerous studies about several designs of the microstrip resonator to improve the sensor performance in terms of the sensitivity and accuracy. This technique enables its use for several industrial applications such as agriculture and quality control. It is believed that previous studies would lead to a promising solution of characterizing materials with high sensitivity, particularly in determining a high Q-factor resonator sensor.